DBD Enterprise Sdn Bhd: A B2B Business model / Diana Zainal - Zainal, Diana (Faculty of Computer and Mathematical Sciences, 2007)
Globally, web based technology acts as a backbone for the business industries within this digital era. In order to adopt this technology innovation, most organizations are transforming their business style from the brick-and-mortar organizations to the click-and-mortar organizations.